PENINGKATAN KEBERHASILAN SAMBUNGAN TOP-WORKING JAMBU METE (Annacardium occidentale L.) DENGAN APLIKASI ASAM INDOL BUTIRAT / Improve Grafting Success of Top Working on Cashew (Annacardium occidentale L.) by Application of Indole Butyric Acid (IBA) - Ireng Darwati; Rudi Suryadi; M. Syakir (Pusat Penelitian dan Pengembangan Perkebunan, 2017)
Cashew (Annacardium occidentale L.) productivity in Indonesia is still low compared with other cashew producing countries, may be the use of low genetic quality of plant material. On of the efforts to improve the productivity is by using high quality genetic materials, which may be done by implementation of top-working technology. Top-working technology may be used to replace existing plants in the field with superior varieties rapidly through grafting method, without having to uproot the existing plants. Top-working on cashew nut crop is still not much information and the success rate is still relatively low when compared to fruit crops. Information on top-working in cashew is still scarce and with little success. Therefore, it is necessary to study the application of IBA to increase grafting success of top-working on cashew. The study was conducted at Cikampek Experimental Station (ES) from January to June 2016. The rootstock is 7 years old, the varieties used for the scion and rootstock are B02. Cashew tree trunks were cut about 1.2 - 1.5 m above ground level during rainy season. The scion used has a length of ± 15 cm and a diameter of 5 - 7 mm with the dormant bud. The design used was a randomized, single factor, with seven replications. The treatments tested were concentrations of IBA (0, 300, 600, and 900 ppm). The parameters measured were the percentage of grafting success, shoot length, leaves number, khlorophyl, and field determination of compatibility constant (FCC). The results showed that 600 ppm IBA application significantly increased the percentage of grafting success, shoot length, leaves number, and the highest FCC value (87.50%, 12.08 cm, leaf 11.40, and 13.84)Keywords: Annacardium occidentale L., auxin, productivity, percentage of grafting success, top-working AbstrakProduktivitas jambu mete (Annacardium occidentale L.) di Indonesia masih rendah yang disebabkan oleh penggunaan bahan tanaman dari biji dengan mutu genetik yang rendah. Salah satu upaya untuk meningkatkan produktivitas jambu mete adalah penerapan teknologi top-working yaitu teknologi menggantikan tanaman tidak unggul di lapang dengan varietas unggul secara cepat melalui cara penyambungan, tanpa harus membongkar tanaman. Tujuan penelitian adalah mendapatkan konsentrasi IBA yang tepat untuk meningkatkan persentase keberhasilan dan pertumbuhan sambungan top working pada tanaman jambu mete. Penelitian dilakukan di Kebun Percobaan (KP) Cikampek mulai bulan Januari sampai Juni 2016. Varietas yang digunakan untuk batang atas (entres) dan batang bawah yaitu B02, dan batang bawah berumur 7 tahun. Pada musim hujan dilakukan pemotongan batang pohon jambu mete setinggi 1,2 – 1,5 m di atas permukaan tanah. Batang atas yang digunakan berukuran panjang ± 15 cm dan diameter 5 – 7 mm dengan mata tunas yang masih tidur (dorman). Rancangan yang digunakan adalah acak kelompok dengan empat perlakuan dan tujuh ulangan. Perlakuan yang diuji adalah konsentrasi IBA (0, 300, 600, dan 900 ppm). Peubah yang diamati adalah persentase sambungan hidup, panjang tunas, jumlah daun, kandungan klorofil, dan kompatibilitas berdasarkan nilai konstan field determination of compatibility constant (FCC). Hasil penelitian menunjukkan bahwa aplikasi IBA 600 ppm dinilai cukup efisien dan efekftif dalam menghasilkan persentase sambungan hidup, panjang tunas, jumlah daun, dan kandungan klorofil.Kata kunci: Annacardium occidentale L., auksin, produktivitas, persen-tase keberhasilan sambungan, top-working.